Paraoxonase-1 (PON1) activity in serum and various anticoagulated-plasma - Abdullah, Nor Zamzila; Ahmad Sufi, Nur Farhah; A. Talib, Norlelawati; Ku Zaifah, Norsidah; Muhammad, Siti Aeshah @ Naznin; Mohamed, Abdul Hadi (College of Pathologists, Academy of Medicine Malaysia, 2012)

(untitled)
Background: Paraoxonase 1 (PON1) is a high density lipoprotein (HDL) associated enzyme that is known for its function to hydrolyze organophosphate (OPs) into a relatively harmless substance and inhibit oxidative modification of low density lipoprotein (LDL). It is among the commonly studied biochemical markers for cardiovascular diseases. PON 1 activity is usually measured in serum (from plain container) while some other relevant cardiovascular parameters require anti-coagulated plasma. Collection of blood in many types of container may increase the cost and require a larger amount of blood to be collected. Apart from plasma in lithium heparin, the reliability of plasma in other anti-coagulated container such as potassium-citrate, potassium- oxalate/sodium-fluoride and CPDA (from blood collection bag) on PON 1 activity have not yet been clearly ascertained. The aim of this study was to compare and to study the correlation between the PON1 activity in serum and in plasma collected in various anti-coagulated containers. Methods: An experimental study was carried out on 50 volunteers. Blood samples were collected in plain container and containers with potassium-EDTA, lithium-heparin, potassium-citrate, potassium-oxalate/sodium-fluoride and CPDA. Serum and plasma were analyzed for PON1 activity spectrophotometrically after the hydrolysis of substrates paraoxon. Results: The PON1 activity in plasma from lithium-heparin container was slightly reduced but not statistically different (p=0.062) from that of serum (272.95U/L±85.11 vs 288.95±91). However, the PON1 activity was significantly reduced (p<0.001) to 224.13±74.78 U/L, 211.46±64.18 U/L, 184.32±60.06 U/L and 48.00±45.91 U/L respectively in plasma from potassium-citrate, CPDA, potassium-oxalate/sodium-flouride and potassium-EDTA container. There were significant positive correlations (p<0.001) between PON1 activity in serum with PON1 activity in all anti-coagulated plasma except for plasma in potassium-EDTA container (r=0.27, p=0.06). Conclusion: Our finding suggested that only serum and plasma in lithium-heparin container are suitable for the analysis of PON1 activity.